Effects of microplastics on greenhouse gas emissions and the microbial community in fertilized soil - Ren, Xinwei; Tang, Jingchun; Liu, Xiaomei; Liu, Qinglong (Environmental pollution (1987), 2020)
Microplastics (MPs) are characterized by small particle sizes (<5 mm) and are widely distributed in the soil environment. To date, little research has been conducted on investigating the effects of MPs on the soil microbial community, which plays a vital role in biogeochemical cycling. In the present study, we investigate the influence of two particle sizes of MPs on dissolved organic carbon (DOC) and its relative functional groups, fluxes of greenhouse gases (GHGs), and the bacterial and fungal communities in fertilized soil. The results showed that a 5% concentration of MPs had no significant effect on soil DOC, whereas the formation of aromatic functional groups was accelerated. In fertilized soil, the existence of MPs decreased the global warming potential (GWP) as a result of a reduction in N2O emissions during the first three days. A potential mechanism for this reduction in N2O emissions might be that MPs inhibited the phylum Chloroflexi, Rhodoplanes genera, and increased the abundance of Thermoleophilia on day 3. An increase in N2O emissions was observed on day 30, mainly due to the acceleration of the NO3− reduction and a decrease in the abundance of Gemmatimonadacea. The CH4 uptake was significantly correlated with Hyphomicrobiaceae on day 3 and Rhodomicrobium on day 30. In soil with MPs, Actinobacteria replaced Proteobacteria as the dominant phylum. Larger MPs increased the richness (Chao1) and abundance-based coverage estimators (ACE) and diversity (Shannon) of the bacterial community on day 3, whereas these decreased on day 30. The richness and diversity of the fungal community were also reduced on days 3 and 30. Smaller MPs increased the community richness and diversity of both bacterial and fungal communities in fertilized soil. Our findings suggest that MPs have selective effects on microbes and can potentially have a serious impact on terrestrial biogeochemical cycles. [Display omitted] •Smaller particle size microplastics could accelerate the aromatic matters’ formation.•Microplastics in fertilized soil could reduce N2O emission.•Actinobacteria replaced Proteobacteria as the Dominant phylum in microplastics soil.•Microplastic size effect was shown on alpha diversity.•Microplastics influenced the co-occurrence network among different microorganisms. Main findings: Microplastics decreased the global warming potential of soil. Particle size affected alpha diversity, and Actinobacteria replaced Proteobacteria as the dominant phylum in soil with microplastics.